User Modeling 1997
DOI: 10.1007/978-3-7091-2670-7_24
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Student Modeling for Coached Problem Solving Using Bayesian Networks

Abstract: Abstract. This paper describes the student modeling component of ANDES, an Intelligent Tutoring System for Newtonian physics. ANDES' student model uses a Bayesian network to do long-term knowledge assessment, plan recognition and prediction of students' actions during problem solving. The network is updated in real time, using an approximate anytime algorithm based on stochastic sampling, as a student solves problems with ANDES. The information in the student model is used by ANDES' Help system to tailor its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 9 publications
0
93
0
4
Order By: Relevance
“…Jebara [16], uses CHMMS, which are a particular case of Dynamic Bayesian Networks, to perform, first analysis, and then synthesis, of a player's behavior in a game. Conati et al [10] have built an intelligent tutoring system able to perform knowledge assessment, plan recognition and prediction of students' actions during problem solving using Bayesian networks. Jameson [15], provides a useful overview of student modeling techniques, and compares the Bayesian network approach with other popular modeling techniques.…”
Section: Bayesian Network For User Modeling and Interactive Narrativementioning
confidence: 99%
“…Jebara [16], uses CHMMS, which are a particular case of Dynamic Bayesian Networks, to perform, first analysis, and then synthesis, of a player's behavior in a game. Conati et al [10] have built an intelligent tutoring system able to perform knowledge assessment, plan recognition and prediction of students' actions during problem solving using Bayesian networks. Jameson [15], provides a useful overview of student modeling techniques, and compares the Bayesian network approach with other popular modeling techniques.…”
Section: Bayesian Network For User Modeling and Interactive Narrativementioning
confidence: 99%
“…Different graphical models, such as Bayesian networks, dependency networks, inference networks, and causal models, have been used to model computer software users (Horvitz et al, 1998), car drivers (Pynadath & Wellman, 1995), students (Conati et al, 1997) and other social phenomena (McKim & Turner, 1997). Choosing the graphical modelling approach as a unified framework to combine multiple forms of evidence is motivated by the prior research.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Third, it can easily combine prior knowledge (such as partial information about the causal relationship) with data. This approach has been applied to model computer software users (Horvitz et al, 1998), car drivers (Pynadath & Wellman, 1995), and students (Conati et al, 1997).…”
Section: Graphical Models For Adaptive Complex User Modelingmentioning
confidence: 99%
“…To this end, we have used a Bayesian student model (BSM) based on Bayesian Networks (BNs). The BN paradigm was chosen because it has proven to be a sound methodology for the student modeling problem, and it has been used with this purpose in a number of existing applications (Collins et al, 1996;Conati et al, 1997;VanLehn et al, 1998;Jameson, 1996). This previous research has shown that a BSM allows for a sound and detailed evaluation of each student, according to the granularity level defined by teachers.…”
Section: Introductionmentioning
confidence: 99%